On Simulium (Pternaspatha), with description of a new species (Diptera-Simuliidae) - Coscarón, Sixto (1996)
Simulium (Pternaspatha) diamantinum n. sp. is described from females, males, pupae and larvae, collected at Mendoza, San Juan and Neuquén. Some specimens of this species from Laguna del Diamante were included before by Wygodzinsky and Coscarón (1967) in S. strigidorsum Enderlein. The new species is compared with closely related species of the S. (Pternaspatha) "nigristrigatum group". The following synonym is established: Simulium (Pternaspatha) bachmanni Wygodzinsky & Coscarón = Simulium (Pternaspatha) nigristrigatum (Enderlein).